Studies in Teaching: 2013 Research Digest - (:unkn) unknown (Wake Forest University, 2025)
This document presents the proceedings of the 18th Annual Research Forum held June 26, 2013, at Wake Forest University in Winston-Salem, North Carolina. Included are the following 13 action research papers: (1) Developing Oral Language Ability in the Secondary Spanish Classroom Using the Interpersonal and Presentational Modes of Communication (Sophia Bauers); (2) Problem-Based Learning and Student Attitudes in Mathematics (Caitlin Boone); (3) "Gramma-Drama": An Exploration of Teaching Grammar through Performing Arts (Kaylin Bugica); (4) Mining for Gold on the Silver Screen: Using Film to Develop Active Literacy Skills (Beau Burns); (5) Influences of Reflective Writing in High School Biology (Laurel Clapp); (6) Multicultural Perspective Taking in Social Studies Education (Angelina Cobb); (7) Using Primary Sources to Evoke Historical Empathy (Christina Cobb); (8) Computers and Problem-Based Learning in Mathematics (Hannah Everhart); (9) Developing Empathy through Identity Enactment Techniques (Caroline Fisher); (10) Literature 2.0: An Exploration of Character using Edmodo (Christina McClain); (11) Flipping the High School Mathematics Classroom (Allison Mousel); (12) Environmental Literacy Meets English: How Students Think about Sense of Place in the Classroom (Michael Short); and (13) How Implementing Interactive Geometric Software Affects Students' Achievement, Engagement, and Attitude Towards Mathematics (Matthew Tysinger). (Individual papers contain references, tables, and figures.)
Action Research Projects Presented at the 18th Annual Graduate Student Research Forum
Keywords: Action Research; Biology; Classroom Environment; Classroom Techniques; Computer Uses in Education; Conferences (Gatherings); Courseware; Environmental Education; Film Study; Geometric Concepts; Grammar; Language Aptitude; Learner Engagement; Literacy; Mathematics Education; Mathematics Instruction; Multicultural Education; Oral Language; Primary Sources; Problem Based Learning; Reflective Teaching; Research Projects; Research Reports; Skill Development; Social Studies; Spanish; Student Attitudes; Teaching Methods; Theater Arts; Values Education; Writing Strategies